Statins modulation of influenza virus H1N1 infection in MDCK cells by molecular signaling pathways - Mehrbod, Parvaneh (2013)
Influenza virus infection still remains a major cause of morbidity and mortality Recently, to lessen influenza infection and increase its efficient treatment, researchers worldwide are developing novel drugs as well as evaluating existing drugs with pleiotropic effects that are able to inhibit the replication and life cycle of influenza viruses. Influenza A virus is a multi-step infectious agent that can induce or inhibit different pathways inside the host cell by recruiting the host machinery system to support the virus replication and induce tissue destruction. One of these pathways is cytokine overexpression following infection which causes hypercytokinemia. This process affects different GTPase proteins isoprenylation. Theses GTPase proteins are involved in different pathways such as endocytosis and actin cytoskeleton polymerization. Another important pathway is autophagy and lysis, where activation of autophagy could also be an effective way of eliminating influenza A virus. Anti-inflammatory and immunomodulatory agents might be beneficial as effective alternative to vaccines and antivirals against influenza virus. Statins as antiinflammatory agents are competitive inhibitors of the enzyme HMG-CoA reductase,which is the enzyme responsible for the rate determining step early in the cholesterol biosynthesis. By inhibiting HMG-CoA reductase, statins block the synthesis of isoprenoid intermediates, which serve as lipid attachments for GTPase signaling molecules. Therefore, the inhibition of their proper membrane localization may play an important role in biological effects of statins to affect downstream molecular signaling pathways. The present study was designed to determine whether statins could affect viral cellular infection via their effect on cholesterol biosynthesis and inhibition of membrane GTPase molecules prenylation and if they can inhibit endocytosis and induce autophagy. Common detection methods used in this study like HA, MTT, ELISA, q-PCR and SDSPAGE along with Western blotting and immunofluorescence techniques indicated statins inhibitory effects on influenza replication. Statins decreased the HA titer and increased the cell viability in different combined treatments with the virus (P≤0.05 & P≤0.01) as compared to the influenza virus treatment. They also induced morphological changes on the virus. Data also showed that statins can limit immune system over expression significantly by decreasing the inflammatory reactions based on inhibitory effects on two important proinflammatory cytokines; IL-6 and TNF-α. The level of viral and cellular target genes copy numbers from statins and virus combined treatments obtained from q-PCR absolute quantification assay showed substantial decrements in majority of the combined treatments (P≤0.001). The quantification of cytokines by q-PCR was confirmed by ELISA. The results even indicated the potential of influenza A virus to induce the pro-inflammatory cytokine secretions in CrFK cells at higher levels than MDCK cells which support the growth of certain influenza virus strains to some extent. The inhibitory effect of statins was verified by detecting Rabs and RhoA proteins prenylation. The expression level of prenylated form of Rabs and RhoA proteins in statin and combined treatments of H1N1 detected through Western Blotting were significantly different from H1N1 treatment (P≤0.001). Statins promoted delocalization of Rabs and RhoA proteins from membranous fraction to cytosol. By contrast, influenza A virus promoted their localization from cytosol to membrane. Statins also induced remarkable morphological changes in the assembly of actin cytoskeleton by inhibiting RhoA protein isoprenylation which is an important factor for actin filaments polymerization. The results detected by fluorescent staining showed that,despite the virus inoculation which caused condensation of the actin filaments, statins induced destruction in their assembly which is effective on the virus transportation inside the cell. In addition; the effect of statins was hindered by pre-exposure of cells to statin inhibitors namely FPP and GGPP as downstream intermediates of cholesterol biosynthesis pathway. Additionally, the fluorescent staining study showed that both statins and virus exposure to the cells caused increments in the lysosomal mass but not significantly different from control (P≥0.05). Statins and influenza A virus have similar effect on autophagy but in different ways. Statins act directly on LC3 lipidation as a reliable marker of autophagosome formation and increase autophagosome formation or delivery to lysosomes, however, influenza A virus acts through its M2 protein channel to inhibit the maturation of autophagosome during autophagy. Hence, statins can act as double-edged swords which enhance autophagy by decreasing the cholesterol synthesis;however, this event may cease intracellular destruction of virus due to inability of autophagosome to undergo maturation. Nevertheless, the results obtained in this study support the potential and capacity of statins as new strategy and effective regimen to control influenza A virus infection. However, further studies are recommended to define more involved pathways and underlying mechanisms of statins as anti-influenza agents and its clinical application in treating humans infected with influenza virus.